Barreras y fuerzas impulsoras de la implementación de la Industria 4.0 en las organizaciones: un estado del arte - León-García, Omar Alexánder; Bermúdez-Segura, Mónica Yamile (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Industry 4.0 is a manufacturing concept that has gained strength in organizations because it delves into industrial automation, digitization, and new technology implementation to improve working conditions and productivity. This article aims to contribute to the current debate on industry 4.0 while providing an overview of barriers and facilitators. Based on documentary analysis of 49 articles written between 2014 and 2020, six categories related to barriers were identified: security, costs, human talent, organizational resistance, and use of technologies; and eight as driving forces of Industry 4.0 implementation: technological pre-existence, management commitment, efficiency, competitiveness, sustainability, competent employees, and government policies.